Pengaruh Penggunaan Aplikasi Desmos Graphing Calculator Terhadap Kemampuan Pemahaman Konsep Matematis Siswa - Durriah Hasibuan; Asrul Asrul; Machrani Adi Putri Siregar (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
The research that has been conducted is entitled "The Effect of the Use of Desmos Graphing Calculator Application on Students' Ability to Understand Mathematical Concepts" which is based on the background that students' ability to understand mathematical concepts is obtained information that it is not optimal so that students do not master the material well. The methodology of this study uses a quantitative type of quasi-experimental research with a posttest test in two classes. The population of this study is all class X students at PAB 1 Medan Estate Private High School with a total of 48 people. Which is divided into X Mia1 and X Mia II. Data sampling technique with saturated samples. Data analysis was carried out with a posttsest test in both classes. Based on the results of the research, it can be concluded that "The Effect of the Use of the Desmos Graphing Calculator Application on the Ability to Understand Mathematical Concepts of Students, the results of data analysis show that the ability to understand mathematical concepts in learning using the Desmos Graphing Calculator media is higher than the ability to understand mathematical concepts in learning without using the Desmos Graphing Calculator media". on the ability to understand mathematical concepts.